Early detection of Y chromosome microdeletions in infertile men is helpful to guide clinical reproductive treatments in southwest of China. Issue 5 (February 2019) - Liu, Ting; Song, Yu-Xin; Jiang, Yong-Mei
Abstract : Abstract: The microdeletions of azoospermia factor (AZF) genes in Y chromosome are greatly associated with male infertility, which is also known as the second major genetic cause of spermatogenetic failure. Accumulating studies demonstrate that the different type of AZF microdeletions in patients reflect different clinical manifestations. Therefore, a better understanding of Y chromosome microdeletions might have broad implication for men health. In this study, we sought to determine the frequency and the character of different Y chromosome microdeletion types in infertile men in southwest of China. In total, 1274 patients with azoospermia and oligozoospermia were recruited in southwest of China and screening for Y chromosome microdeletions in AZF regions by multiplex polymerase chain reaction. The incidence of AZF microdeletions in southwest of China is 12.87%, which is higher than the national average. Further investigations unveiled that azoospermia factor c (AZFc) is the most frequent type of all the AZF microdeletions. Additionally, the number and also the quality of sperm in patients with AZFc microdeletion is decreasing with the age. Therefore, it is conceivable that the early testing for Y chromosome microdeletions in infertile men is crucial for fertility guidance. The early detection of Y chromosome microdeletions in infertile men can not only clearly explain the etiology of oligzoospermia and azoospermia, but also help for the clinical management of both infertile man and his future male offspring.